Histological evaluation of nephroprotective effect of Solanum nigrum fruit extract against gentamicin induced nephrotoxicity in experimental rats - Kushwaha, Vimlesh (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Drug induced nephrotoxicity, one of the most common renal problem, is a challenge to deal with especially in patients with renal dysfunction. It is responsible for 20% cases of acute renal failure in the community. Modern medicines are costly and have minimal nephroprotection. Solanum nigrum fruit extract, a cheaper drug, have antioxidant property and may help in nephroprotection. Methods: Total 54 rats were randomised in 3 groups named G10, G20 and G30 according to 10, 20 and 30 days of treatment. In each groups, rats were randomly assigned to any of the three subgroups i.e., control C group [received normal saline (2 ml/100 gm/day) orally consecutively for test duration], gentamicin treated (GT) group [received normal saline (2 ml/100 gm/day) orally consecutively for test duration and intraperitoneal gentamicin (40 mg/kg) once daily for last five days] and S. nigrum treated (SNT) group [received S. nigrum orally (200 mg/kg/day) for the test duration and intraperitoneal gentamicin (40 mg/kg) once daily for last five days]. Rats were sacrificed 24 hours after the last dose of gentamicin injection (on 11th, 21st and 31st day). Excised kidneys were weighted and prepared for histological examination. Results: The mean weight of kidneys in GT group was significantly higher than the SNT group in all test durations suggestive of decrease in inflammation in SNT group. This was also reflected histologically as SNT group kidney showed less amount of tubular destruction as compared to GT group. Conclusions: S. nigrum extract provide nephroprotection against gentamicin induced nephrotoxicity.